Iron-chromium-nickel-aluminum high-temperature alloy material and application method thereof
By using a new iron-chromium-nickel-aluminum high-temperature alloy material with specific element ratios in the ethylene radiation furnace tube material, the problem of insufficient coking, oxidation and high-temperature durability of the existing materials in high-temperature environments is solved, and the material's efficient antioxidation and long-term high-temperature stability is achieved.
Patent Information
- Application Number
- CN202510230695.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-28
AI Technical Summary
The existing ethylene radiation furnace tube materials have insufficient coking, oxidation and long-lasting properties in high-temperature environments, resulting in a decrease in heat conduction efficiency, accelerated material aging and increased safety hazards.
A new iron-chromium-nickel-aluminum high-temperature alloy material is used, which contains elements of a specific proportion such as carbon, manganese, silicon, chromium, nickel, aluminum, etc. By regulating the content and composition of these elements, a stable oxide film and carbide precipitation is formed, enhancing the high-temperature creep resistance and corrosion resistance of the material.
It significantly improves the material's anti-coking performance, anti-oxidation performance and high-temperature long-lasting performance, extends the service life of the furnace tube, reduces the time for shutdown and cleansing of the furnace, and improves the operating efficiency and economic benefits of the ethylene radiation furnace.
Smart Images

Figure CN119710371A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of iron-chromium-nickel-aluminum high-temperature alloy materials, and in particular to an iron-chromium-nickel-aluminum high-temperature alloy material that can be used as a furnace tube material for an ethylene radiation furnace. Background Art
[0002] Ethylene radiation furnace is a key equipment for producing ethylene. It converts raw materials into chemical products such as ethylene and propylene through high-temperature cracking (900-1200℃). However, during the cracking process, carbon and coke deposition will form on the inner wall of the furnace tube, resulting in reduced heat transfer efficiency, increased furnace tube wall temperature, increased operating pressure and other problems, increasing energy consumption, accelerating material aging and posing safety hazards. The decoking cycle of modern ethylene plants is usually 30-90 days, and the decoking process requires shutdown, which directly affects operating efficiency and economic benefits. Therefore, reducing the coking rate, extending the operating cycle, and reducing the shutdown time for decoking are crucial to improving economic benefits.
[0003] On the other hand, ethylene radiation furnaces have high requirements for furnace tube materials, which usually need to have the following characteristics: (1) high temperature strength, which can withstand the high temperature conditions of the cracking reaction and have excellent creep strength; (2) anti-coking performance, such as improving the inertness of the surface, that is, reducing the contact and reaction between carbon atoms and Fe and Ni metals at high temperatures; (3) corrosion resistance to cope with the corrosion and carburization of the furnace tube materials by the corrosive gases generated during the cracking process; (4) long service life, reducing downtime, and improving the reliability and stability of the device operation.
[0004] At present, when the temperature of high-temperature alloy furnace tubes with iron, chromium and nickel (FeCrNi) as the main components exceeds 900℃, the surface chromium oxide layer will become unstable, resulting in the gasification or decomposition of oxide scale, accelerating the coking and carburization problems, and significantly affecting the life of the furnace tube. Some existing technologies have improved it. For example, the iron-chromium-nickel-aluminum high-temperature alloy proposed in the existing patent technologies US 8431072 and US8815146 can make the furnace tube operate well under the working conditions of 600℃ to 900℃ by adding an alumina protective layer, but it cannot further meet the needs of high-temperature environments of 900℃ to 1200℃; and the high-temperature material with high aluminum content centrifugally cast provided by patent EP0169119A1 has improved the anti-oxidation performance through the alumina protective layer, but its coking speed and high-temperature durability still cannot fully meet the actual needs.
[0005] In summary, the existing ethylene radiation furnace tube materials still have deficiencies in anti-coking performance, anti-oxidation performance and high-temperature durability under high-temperature environments. It is urgent to develop a new material to solve the above problems and improve the operating efficiency and economic benefits of the ethylene radiation furnace. Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present invention is to propose a new type of iron-chromium-nickel-aluminum high-temperature alloy material with significantly improved anti-coking performance, anti-oxidation performance and high-temperature durability, which can significantly improve the operating efficiency and economic benefits of ethylene radiation furnaces.
[0007] The technical solution of the present invention is as follows: An iron-chromium-nickel-aluminum high-temperature alloy material, comprising the following elements: carbon, manganese, silicon, chromium, nickel, aluminum, niobium, titanium, tungsten, iron, molybdenum, nitrogen, calcium, tantalum, zirconium, hafnium, yttrium and cerium, wherein the mass percentage of carbon element is 0.4-0.6wt%, the mass percentage of nickel element is 38-50wt%, the mass percentage of chromium element is 23.0-32.0wt%, the mass percentage of manganese element is less than 2wt%, the mass percentage of silicon element is 0.1-1.5wt%, the mass percentage of aluminum element is 3.0-5.0wt%, the mass percentage of niobium element is 0.5-1.5wt%, the mass percentage of tungsten element is 0.01-1wt%, the mass percentage of molybdenum element is 0.01-0.1wt%, the mass percentage of tungsten ... The mass percentage of the element is 0.01-1wt%, the mass percentage of the element titanium is 0.05-0.2wt%, the mass percentage of the element nitrogen is 0.005-0.2wt%, the mass percentage of the element calcium is 0.001-0.5wt%, the mass percentage of the element yttrium is 0.001-0.5wt%, the mass percentage of the element cerium is 0.001-0.5wt%, the mass percentage of the element tantalum is 0.01-0.5wt%, the mass percentage of the element zirconium is 0.01-0.5wt%, the mass percentage of the element hafnium is 0.001-0.5wt%, and the mass percentage of the element chromium, aluminum, and nickel satisfy the following calculation model: f The value of (x) is less than 3%:
[0008] in, f (x) represents the volume percentage of NiAl precipitated phase in the material, b1 represents the overall scaling parameter, b2 represents the influence coefficient of chromium, b3 represents the influence coefficient of aluminum, b4 represents the influence coefficient of nickel, b5 is a constant term, and b6 represents the exponential attenuation factor of temperature effect, and its values are: b1=1.5419, b2=-0.5839, b3=3.4687, b4=-1.3242, b5=61.3191, b6=0.2286; X cr Indicates the mass percentage of chromium, X Al Indicates the mass percentage of aluminum element, X Ni represents the mass percentage of nickel element, and T represents the absolute temperature (K) when the iron-chromium-nickel-aluminum high-temperature alloy material is used.
[0009] In the above scheme of the present invention: Carbon plays an important role in high-temperature alloys. It enhances the high-temperature creep resistance of the material through carbide precipitation and also has a significant impact on the fluidity of molten steel.
[0010] Aluminum can form a dense aluminum oxide film in high-temperature alloy casting, which improves the alloy's high-temperature resistance, oxidation resistance and carburization resistance. To ensure the sustainability and integrity of the aluminum oxide film, the aluminum content in the alloy is best maintained above 2%. If the aluminum content exceeds 7%, a large number of irregular, microscopically huge precipitates will appear in the alloy, affecting the alloy's grain structure and reducing the material's comprehensive mechanical properties. Therefore, preferably, the aluminum content should be in the range of 3-5%.
[0011] Chromium can also form an oxide film or form a composite oxide film with aluminum oxide that has excellent high-temperature oxidation resistance, effectively protecting the metal matrix from oxidation and corrosion. At the same time, in the process of carbide precipitation, chromium is a carbide precipitate. 23 The main component of C6 enhances the high temperature strength and creep resistance of the alloy. The inventor unexpectedly found that if the chromium content exceeds 35%, and nickel and aluminum are present in the material at the same time, an unfavorable Sigma phase may be formed in the alloy, which will reduce the mechanical properties of the material. Therefore, the preferred content of chromium can be maintained between 23-32% to ensure a good balance between oxidizability, corrosion resistance and mechanical properties of the material.
[0012] Nickel is one of the key elements in casting high-temperature alloys. The presence of sufficient nickel helps stabilize austenite (CFC face-centered cubic structure), thereby giving the alloy high-temperature toughness and plasticity. At the same time, it promotes the precipitation of carbides, improves the durability and corrosion resistance of the alloy, and then, nickel is the main catalytic matrix in the coking process, and too high a nickel content may accelerate the coking process.
[0013] The inventor unexpectedly found that when the nickel content exceeds 50%, in a high-temperature olefin environment, although the alloy surface is covered with an aluminum oxide film, the coking speed on the surface will be significantly accelerated. Therefore, controlling the nickel content below 50% can effectively slow down the coking speed in a cracking environment and reduce the cost of raw materials. At the same time, the increase in nickel content helps to inhibit the precipitation of Sigma phase, which should not be less than 35%. Therefore, keeping its content at 38-50% can improve the high-temperature performance of the material.
[0014] The role of silicon in high-temperature alloys includes deoxidizing molten steel, improving fluidity, and improving the stability of the oxide film through the formation of silicon oxide, thereby enhancing the alloy's antioxidant capacity. However, when the silicon content is too high, the deformation performance of the material at high temperatures will be reduced, affecting the overall plasticity of the alloy. Therefore, the silicon content should be controlled within the range of 0.1-1.5wt%.
[0015] The role of manganese in high-temperature alloys includes deoxidation and controlling the sulfur (S) content, thereby improving the purity of the material. However, too high a manganese content will have an adverse effect on the creep properties of the material and reduce the alloy's high-temperature durability. Therefore, controlling it below 2% can ensure the best performance of the alloy.
[0016] The role of rare earth elements such as hafnium, yttrium and cerium in high-temperature alloys includes improving the stability of the oxide scale and enhancing the bonding strength between the oxide scale and the matrix material interface, thereby improving the long-term service performance of the material in a high-temperature environment. The inventor unexpectedly discovered that the content should be controlled within the range of 0.001-0.5% to ensure the best high-temperature resistance of the material.
[0017] Tungsten can enhance the alloy's long-term strength and improve the material's high-temperature stability through solid solution strengthening at high temperatures (about 1100°C). However, the inventors unexpectedly discovered that excessive tungsten content may lead to the precipitation of LAVES and Sigma. The growth of these precipitates will affect the material's long-term performance and plasticity, and interfere with the diffusion of aluminum (Al) in the material, thereby reducing the long-term stability of the oxide film. Therefore, the tungsten content needs to be controlled at 0.01-1% to ensure the best performance of the alloy.
[0018] Molybdenum can improve the high-temperature durability of the alloy through solid solution strengthening, and enhance the stability and durability of the material in high-temperature environments. The inventors unexpectedly discovered that controlling its content within the range of 0.01-1% can ensure the best high-temperature performance of the alloy.
[0019] Niobium is mainly precipitated in the form of carbide MC, which can significantly enhance the durability of the material and has an important influence on the high-temperature creep performance of the material. It is one of the important elements to improve the high-temperature resistance of the alloy. The inventor unexpectedly found that the niobium content is controlled within the range of 0.5-1.5% to ensure that the alloy has better durability and high-temperature creep resistance.
[0020] The addition of titanium can not only enhance the creep resistance of the alloy, but also improve the fatigue resistance and crack resistance of the material, thereby extending its service life. 23 C6 has good thermal stability and can effectively inhibit grain coarsening and softening. The inventor unexpectedly discovered that controlling the titanium content within the range of 0.05-0.2% can ensure that the material has the best high-temperature mechanical properties.
[0021] Nitrogen can significantly enhance the high temperature strength and durability of the material by precipitating nitrides in the alloy, and improve the alloy's deformation resistance and fatigue resistance. However, when its content is too high, it may have an adverse effect on the plasticity of the material, resulting in a decrease in the high temperature stability of the alloy. The inventor unexpectedly found that controlling the nitrogen content within the range of 0.005-0.2% can ensure that the material maintains good creep performance while improving the high temperature strength.
[0022] Calcium, as a strong desulfurization and deoxidizer, can effectively reduce the sulfur and oxygen content in molten steel, thereby significantly improving the purity of the alloy and enhancing the corrosion resistance and durability of the material in a high temperature environment. The inventor unexpectedly discovered that controlling the calcium content in the range of 0.001-0.5% can ensure that the material has the best desulfurization and deoxidation effect and improve the overall performance of the material.
[0023] Tantalum can significantly increase lattice distortion in the solid solution of high-temperature alloys, thereby producing a strong solid solution strengthening effect. This strengthening mechanism can effectively improve the high-temperature strength and creep resistance of the alloy, allowing it to maintain good mechanical stability under extreme service conditions. In addition, tantalum has a strong carbon affinity and can promote the formation of dispersion-strengthened carbides (such as TaC). These high-melting point carbide particles are evenly distributed in the matrix, which can effectively pin dislocation movement, hinder grain boundary sliding and grain growth, and thus significantly improve the high-temperature durability and hardness of the material.
[0024] Zirconium can form stable ZrC carbides with carbon in high-temperature alloys. These dispersed carbides can effectively hinder dislocation movement, thereby significantly improving the high-temperature hardness and creep resistance of the material. In addition, zirconium can also promote other strengthening phases (such as M 23 C6 and MC carbides) are precipitated stably, further enhancing the precipitation strengthening effect of the alloy and improving its high temperature strength and durability. At the same time, during the alloy smelting process, zirconium can form stable oxides or sulfides with impurity elements such as oxygen and sulfur, effectively reducing the content of non-metallic inclusions, thereby improving the purity of the material. This not only improves the casting performance of the alloy and makes its structure more uniform, but also enhances the stability of its mechanical properties, providing more reliable protection for high temperature service.
[0025] On this basis, the inventor unexpectedly found that in the above element composition, especially the co-addition of Al, Cr, and Ni, compared with the traditional precipitate M 23C6 and MC phases will also form NiAl and BCC phases. Among them, NiAl is a harmful phase that will form micro cracks at the boundary between the matrix and NiAl phase of the alloy. The micro cracks will further expand with the increase of NiAl content, resulting in an increase in the macro crack tendency of the material. At the same time, with the increase of NiAl phase content, BCC phase will gradually appear at the position of NiAl grain boundary, further aggravating the crack tendency of the material. Therefore, in order to improve the high-temperature creep performance of the material, it is necessary to control the volume percentage (Fraction) of NiAl within a lower range, which will also suppress the appearance of BCC phase. The inventor unexpectedly found that within a specific element range, the calculation model can better predict the volume percentage of NiAl precipitation phase appearing in the material at high temperature such as 900-1200°C through Al, Cr, Ni content and some measurement parameters, avoiding the crack tendency caused by NiAl precipitation phase, thereby improving the high-temperature creep resistance of the furnace tube.
[0026] The inventors also unexpectedly discovered that the calculation model can be applied to high-temperature alloys with an Al content of 3-5%, a Cr content of 23-32%, a Ni content of 38-50%, and an application temperature of 900-1200°C.
[0027] It should be noted that, because another precipitated phase BCC phase that damages the high temperature performance of the material will be formed at the grain boundary between the NiAl phase and the parent material matrix, the BCC phase will only appear when the volume fraction of the NiAl phase is high. Therefore, the technical solution of the present invention controls the content of the NiAl phase in a relatively low range, and can also effectively inhibit the generation of the BCC phase.
[0028] The inventor unexpectedly discovered that when f When the value of (x) is less than 3%, the material can have good high-temperature creep and excellent comprehensive mechanical properties in the high temperature range of 900-1200℃, meeting the current engineering equipment design requirements.
[0029] Preferably, the inventors unexpectedly discovered that when f When the value of (x) is less than 1%, the material can show high-temperature and long-lasting performance in the high temperature range of 900-1200℃. The fracture time of high temperature test under the same conditions is f (x) = 3% further improved by 3 to 6 times.
[0030] According to some preferred embodiments of the present invention, the iron-chromium-nickel-aluminum high-temperature alloy material contains impurity elements with a mass percentage of less than 400 ppm and a balance of iron, and the impurity elements include sulfur elements with a mass percentage of less than 100 ppm and phosphorus elements with a mass percentage of less than 300 ppm.
[0031] In the above preferred embodiment, phosphorus is an impurity element that is concentrated at the grain boundary, which will significantly reduce the plasticity and toughness of the alloy, increase the brittleness of the material, and easily lead to brittle fracture, especially in high or low temperature environments. In addition, the presence of phosphorus will promote the weakening of the grain boundary, reduce the creep performance and endurance strength of the material, thereby affecting the long-term service ability of the high-temperature alloy. During the welding process, phosphorus will also increase the sensitivity of hot cracks, affecting the quality of the weld and the reliability of the joint.
[0032] Sulfur exists in the alloy mainly in the form of sulfides, which easily form compounds such as Ni3S2 with low melting points. These compounds will precipitate along the grain boundaries, causing grain boundary cracking of the alloy during high-temperature service, thereby reducing the endurance strength and creep performance. In addition, sulfide inclusions will reduce the metallurgical purity of the alloy and affect the casting and mechanical performance stability.
[0033] According to some preferred embodiments of the present invention, in the iron-chromium-nickel-aluminum high-temperature alloy material, the mass percentage of carbon element is 0.45-0.55wt%, the mass percentage of manganese element is below 0.5wt%, the mass percentage of silicon element is 0.5-0.9wt%, the mass percentage of chromium element is 24-31wt%, the mass percentage of nickel element is 44-47wt%, the mass percentage of aluminum element is 3.5-4.5wt%, the mass percentage of niobium element is 0.7-0.9wt%, the mass percentage of titanium element is 0.1-0.15wt%, the mass percentage of tungsten element is 0.5-0.8wt%, and the mass percentage of tantalum element is 10-15wt%. The mass percentage of zirconium element is 0.1-0.2wt%, the mass percentage of yttrium element is 0.05-0.1wt%, the mass percentage of cerium element is 0.05-0.1wt%, the mass percentage of molybdenum element is 0.05-0.5wt%, the mass percentage of nitrogen element is 0.05-0.1wt%, the mass percentage of hafnium element is 0.05-0.1wt%, the mass percentage of calcium element is 0.01-0.2wt% and the remainder of iron excluding impurities, the mass percentage of impurities is less than 130ppm, including less than 30ppm of sulfur element and less than 100ppm of phosphorus element.
[0034] The inventor unexpectedly discovered that when the iron-chromium-nickel-aluminum high-temperature alloy material is obtained within the above range and under high-temperature working conditions, its furnace tube surface coking rate is lower than that of iron-chromium-nickel, while its high-temperature endurance performance is more than twice that of general iron-chromium-nickel high-temperature alloy materials.
[0035] The invention further discloses a method for applying the iron-chromium-nickel-aluminum high-temperature alloy material to a furnace tube of an ethylene radiation furnace.
[0036] For example, in some preferred embodiments, the application includes: forming the iron-chromium-nickel-aluminum high-temperature alloy material into an ethylene radiation furnace tube and performing a pre-oxidation treatment.
[0037] The inventors unexpectedly discovered that when the iron-chromium-nickel-aluminum high-temperature alloy material is pretreated in an optimized oxygen partial pressure environment, the stability of the oxide scale can be enhanced, the quality of the oxide film can be effectively improved, and the service life of the furnace tube in a high temperature and high oxygen environment can be extended.
[0038] Preferably, the pre-oxidation treatment is carried out at a temperature of 900° C. for a period of 12-36 hours.
[0039] Preferably, the oxygen partial pressure of the pre-oxidation treatment is 10 -27 bar below.
[0040] With respect to the above preferred embodiments, the inventors unexpectedly discovered that by creating a high temperature and low oxygen partial pressure environment, the oxidation order of the surface of the Fe-Cr-Ni-Al high temperature alloy material can be changed. In order to preferentially form a complete and dense aluminum oxide film, the oxidation order of the surface of the Fe-Cr-Ni-Al high temperature alloy material can be changed by creating a high temperature and low oxygen partial pressure environment. -27 An oxidation reaction is carried out in a bar environment to obtain a stable aluminum oxide film, and after it is stabilized, a chromium oxide film is formed.
[0041] With respect to the above preferred embodiments, the inventors unexpectedly found that within the Al content range of the present invention, the oxygen partial pressure has a significant effect on the thermal stability and fatigue resistance of the oxide scale. -27 When the temperature is below bar, the thermal stability of the oxide scale is significantly poor, which can easily lead to the destruction of the oxide film and accelerated oxidation of the material.
[0042] The present invention has the following beneficial effects: (1) The present invention provides a new FeCrNiAl-based alloy that can replace the traditional FeCrNi-based alloy, which can significantly reduce the coking rate of furnace tubes while maintaining relatively excellent high-temperature endurance performance (equivalent to or better than the current mainstream European standard EN 1.4889 high-temperature alloy); (2) The present invention solves the problem of high nickel content in existing alloys leading to easy catalytic coking on the surface of metal oxide scale by regulating the nickel content in the alloy, and controls the coking rate on the surface of the material at a very low level; (3) The present invention controls the composition ratio of Cr, Ni and Al to inhibit the precipitation of NiAl phase and BCC phase, thereby solving the problem of reduced furnace tube durability due to the precipitation of NiAl phase in existing alloys, and improving and stabilizing the durability of the material; (4) The present invention further solves the local coking problem of existing alloys in high-temperature applications through the pre-oxidation process, provides anti-coking performance of furnace tube oxide scale, and improves the anti-coking performance of furnace tubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a statistical analysis chart of the Ni content of samples 1, 2, 3, 7, 8, and 9 obtained in Example 1 and the weight change after the first coking process.
[0044] Figure 2 This is a statistical analysis chart of the weight changes of samples 1, 2, 4, and 5 obtained in Example 1 after the 50th coking process and the oxygen partial pressure during their pre-oxidation.
[0045] Figure 3 This is a comparison chart of the NiAl phase volume fractions of samples 1, 2, 3, 4, and 5 calculated by the JMatPro software and the F model obtained in Example 2.
[0046] Figure 4 The LMP curve comparison diagram of samples 1, 2, 3, 6 obtained in Example 3 and the existing material ZG50Ni45Cr35NbM is shown.
[0047] Figure 5 This is the backscattered electron mode image of the sampling sample obtained in Example 4 under a scanning electron microscope.
[0048] Figure 6 for Figure 5 Select the element spectrum of region 1.
[0049] Figure 7 for Figure 5 Select the element spectrum of area 2.
[0050] Figure 8 for Figure 5 Select the element spectrum of area 3. DETAILED DESCRIPTION
[0051] The technical solutions in the present invention will be further described below in conjunction with the embodiments of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should belong to the scope of protection of the present invention.
[0052] Example 1 Eleven high-temperature alloy material samples, namely samples 1-11, were prepared according to the compositions in Table 1-2 below: Table 1 Elemental composition of samples 1-5
[0053] Table 2 Elemental composition of samples 6-11
[0054] The samples were all square metal samples with a size of 3 cm×3 cm×3 mm, and the surface roughness was controlled to be less than 3.2 μm through machining.
[0055] All samples were pre-oxidized at 900°C for 24 hours. The pre-oxidation atmosphere and oxygen partial pressure of different samples were as follows: The pre-oxidation atmosphere of samples 1, 3, 6, 7, 8, 9, 10, and 11 was 10 vol% water vapor and 90 vol% inert gas argon, with an oxygen partial pressure of about 10 -27 bar; The pre-oxidation atmosphere of sample 5 was 10 vol% dry air and 90 vol% water vapor, with an oxygen partial pressure of about 10 -10 bar; The pre-oxidation atmosphere of sample 4 was 100 vol% water vapor and the oxygen partial pressure was about 10 -20 bar; The pre-oxidation atmosphere of sample 2 was 2 vol% water vapor and 97 vol% inert gas argon, with an oxygen partial pressure of about 10 -30 bar.
[0056] Thermogravimetric experiments were performed on the pre-oxidized samples to evaluate the coking conditions by the increase in sample mass. Thermogravimetric experiments were performed using a high-temperature tubular heating furnace. The experimental steps included: (1) Heating stage, including: Coking process: at 1150 °C, 30 vol% water vapor and 70% vol% C2H6 atmosphere were introduced for 2 hours; De-coking process: at 950℃, introduce 50%vol steam and 50%vol air atmosphere for 50 minutes; (2) Cooling and weighing stage: After each coking process and each decoking process, inert gas is introduced and the temperature is gradually lowered to room temperature, and then the sample is taken out and weighed.
[0057] The Ni content of samples with different Ni contents (samples 1, 2, 3, 7, 8, 9, 10, and 11) and their weight changes after pre-oxidation and the first coking process were statistically analyzed. The results are shown in the attached figure. Figure 1As shown. By comparing samples 1, 2, 3, 7, 8, and 9, it can be seen that although a dense aluminum oxide film is formed on the surface of the material after pre-oxidation, the growth of MC and M23C6 precipitates near the surface may cause the material matrix to be exposed to a high-temperature environment with a high carbon density, resulting in varying degrees of coking and weight gain. Sample 2 was pre-oxidized at a lower oxygen partial pressure than sample 1, and the density of the aluminum oxide film on its surface should be higher than that of sample 1. However, the carbon deposition rate of sample 2 is still higher than that of sample 1, indicating that the nickel content is the main factor affecting the carbon deposition rate. The results also show that when the Ni content exceeds 50%, the coking rate of the material increases three times. Therefore, controlling the Ni content below 50% can significantly reduce the coking rate. By comparing samples 1, 10, and 11, it can be seen that the weight change of the aluminum-added sample 1 after the first coking process is significantly different from that of the traditional FeCrNi products 10 and 11. The Ni content is not the main reason here. The main reason is that the aluminum oxide film on the surface of the aluminum-added sample 1 is more stable at 1150°C than the traditional chromium oxide film, and the latter undergoes gasification or decomposition reactions at high temperatures, causing the Fe and Ni in the parent material to be exposed to an atmosphere with high solubility of C atoms, thereby accelerating the surface carbon deposition rate.
[0058] Furthermore, samples 1, 2, 4, and 5, which had undergone different pre-oxidation processes and whose Ni contents were all less than 50%, were subjected to the same 50 coking and 49 decoking processes, and the weight changes of the samples after the 50th coking process were statistically analyzed with the oxygen partial pressure during the pre-oxidation. The results are shown in the attached figure. Figure 2 As shown in the figure, the Al and Cr contents of the above samples are similar, so it can be considered that the oxide scale components and compositions of the samples are the same. The only difference is the oxygen partial pressure of the pre-oxidation. Figure 2 The oxygen partial pressure of samples 1 and 2 in pre-oxidation was less than 10 -27 Bar, the coking rate after 50 coking processes is the same and only slightly increased compared to the first coking process. The pre-oxidation oxygen partial pressures of samples 4 and 5 are 10 -20 and 10 -10 Bar, as the oxygen partial pressure increases, the coking speed of the material increases. Therefore, in order to ensure the high temperature performance of the material in an environment greater than 1000℃, the oxygen partial pressure of the pre-oxidation is 10 -27 It is best in a low oxygen and high temperature environment below bar.
[0059] Example 2 The volume fraction of NiAl precipitated phase of samples 1, 2, 3, 4 and 5 at 900° C. in the steady state in Example 1 was calculated using JMatPro software and the F model.
[0060] Among them, JMatPro software is a professional material simulation software widely used to calculate the thermophysical properties and phase change behavior of materials. In the study of precipitation phase, JMatPro can predict the type, volume fraction and stability of precipitation phase of alloy materials under different temperatures, compositions and heat treatment conditions through thermodynamic calculations. In this embodiment, the composition of samples 1, 2, 3, 4, and 5 is brought into the Jmatpro software, and the nickel-based high-temperature alloy database is selected, and the volume percentage of NiAl precipitation phase of the above samples at 900°C steady state can be obtained.
[0061] The F model is calculated as follows:
[0062] in, f (x) represents the volume percentage of NiAl phase, b1 represents the overall scaling parameter, b2 represents the influence coefficient of chromium element, b3 represents the influence coefficient of aluminum element, b4 represents the influence coefficient of nickel element, b5 is a constant term, and b6 represents the exponential attenuation factor of temperature effect, and its values are: b1=1.5419, b2=-0.5839, b3=3.4687, b4=-1.3242, b5=61.3191, b6=0.2286; X cr Indicates the mass content percentage of chromium element, X Al Indicates the mass content percentage of aluminum element, X Ni It represents the percentage of nickel content by mass, and T represents the absolute temperature (K) of the material when it is used at high temperature. Here, the absolute temperature corresponding to 900°C is 1173.5K.
[0063] The calculation results of JMatPro are that the volume fractions of NiAl phase in samples 1, 2, 3, 4, and 5 at 900℃ are 1.19, 3.13, 4.24, 0.13, and 1.19, respectively. The comparison with the calculation results of F model is shown in the attached figure. Figure 3 As shown, it can be seen that the F model is accurate.
[0064] Example 3 Five groups of high-temperature endurance tests were carried out on samples 1, 2, 3, and 6 in Example 1, respectively. The experimental process was as follows: at 950°C, tensile forces of 35 MPa, 30 MPa, and 25 MPa were applied to each sample, respectively; at 1150°C, the sample completed two high-temperature endurance tests under a tensile force of 12 MPa, and its fracture time under different pressures was recorded.
[0065] The volume percentages of NiAl phase of samples 1, 2, 3, and 6 calculated according to the F model at 950°C are 1.04, 3.13, 4.24, and 2.14, respectively.
[0066] The experimental results are shown in Table 3 below: Table 3 High temperature endurance test results
[0067] The above experimental results are compared with the LMP curve of the existing ZG50Ni45Cr35NbM (corresponding to the European standard En 1.4889) heat-resistant and corrosion-resistant alloy. The results are shown in the attached figure. Figure 4 As shown in the figure, it can be seen that in the temperature range of 950-1150℃, when the volume percentage of the NiAl phase of the sample is higher than 3.13%, the high temperature rupture performance of the sample is lower than the minimum value of the LMP curve of the ZG50Ni45Cr35NbM alloy, and as the value increases, the high temperature performance of the material gradually decreases. When the percentage of NiAl precipitation phase in the material is less than or equal to 1%, the high temperature performance of the material is equivalent to or slightly higher than that of ZG50Ni45Cr35NbM.
[0068] At the same time, the results also show that sample 6 has 5% W added. Therefore, although the calculated volume percentage of NiAl phase is 2.14%, its endurance performance is much lower than the minimum value of ZG50Ni45Cr35NbM. The main reason is that there is not only 2.14% NiAl in the base material, but also sigma phase and Laves phase generated by the addition of W element, which reduces the high temperature endurance performance.
[0069] Example 4 Samples were taken from sample 1 after it was broken at 950℃ and 35MPa tension for 890 hours. The sampling position was the end of the sample that was only exposed to high temperature but not tension. The microstructure was observed. The results are shown in the attached figure. Figure 5-8 As shown, Figure 5 This is the image of the backscattered electron mode of the electron scanning microscope. Figures 6 to 8 They are the element energy spectra of selected area 1, selected area 2 and selected area 3 respectively. Figure 6 and Figure 7 Corresponding to M 23 Energy spectra of C6 precipitation phase (M represents a certain metal element, mainly Cr here) and MC (M is mainly Nb here) precipitation phase, Figure 8 It is the energy spectrum of the material matrix. It can be seen that, as predicted by the F model calculation results, no NiAl phase and BCC phase are found in the microstructure of sample 1, and the high-temperature endurance performance of the material is good.
[0070] It should be noted that the above is only a preferred embodiment of the present invention, which should not limit the protection scope of the technical solution of the present invention. Any modification of the technical solution recorded in the above embodiments and equivalent replacement of technical features by ordinary technicians in the field within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An iron-chromium-nickel-aluminum high-temperature alloy material, characterized in that: It includes the following elements: Carbon, manganese, silicon, chromium, nickel, aluminum, niobium, titanium, tungsten, iron, molybdenum, nitrogen, calcium, tantalum, zirconium, hafnium, yttrium and cerium, wherein the mass percentage of carbon element is 0.4-0.6wt%, the mass percentage of nickel element is 38-50wt%, the mass percentage of chromium element is 23.0-32.0wt%, the mass percentage of manganese element is less than 2wt%, the mass percentage of silicon element is 0.1-1.5wt%, the mass percentage of aluminum element is 3.0-5.0wt%, the mass percentage of niobium element is 0.5-1.5wt%, the mass percentage of tungsten element is 0.01-1wt%, and the mass percentage of molybdenum element is 0.01 -1wt%, the mass percentage of titanium is 0.05-0.2wt%, the mass percentage of nitrogen is 0.005-0.2wt%, the mass percentage of calcium is 0.001-0.5wt%, the mass percentage of yttrium is 0.001-0.5wt%, the mass percentage of cerium is 0.001-0.5wt%, the mass percentage of tantalum is 0.01-0.5wt%, the mass percentage of zirconium is 0.01-0.5wt%, the mass percentage of hafnium is 0.001-0.5wt%, and the mass percentage of chromium, aluminum and nickel satisfy the following calculation model: f The value of (x) is less than 3%: ; in, f (x) represents the volume percentage of NiAl precipitated phase in the material, b1 represents the overall scaling parameter, b2 represents the influence coefficient of chromium, b3 represents the influence coefficient of aluminum, b4 represents the influence coefficient of nickel, b5 is a constant term, and b6 represents the exponential attenuation factor of temperature effect, and its values are: b1=1.5419, b2=-0.5839, b3=3.4687, b4=-1.3242, b5=61.3191, b6=0.2286; X cr Indicates the mass percentage of chromium, X Al Indicates the mass percentage of aluminum element, X Ni represents the mass percentage of nickel element, and T represents the absolute temperature when the iron-chromium-nickel-aluminum high-temperature alloy material is used.
2. The iron-chromium-nickel-aluminum high-temperature alloy material according to claim 1, characterized in that: The mass percentages of chromium, aluminum and nickel satisfy the calculation model. f The value of (x) is less than 1%.
3. The iron-chromium-nickel-aluminum high-temperature alloy material according to claim 1, characterized in that: It contains impurity elements with a mass percentage content of less than 400 ppm and the remainder of iron, wherein the impurity elements include sulfur elements with a mass percentage content of less than 100 ppm and phosphorus elements with a mass percentage content of less than 300 ppm.
4. The iron-chromium-nickel-aluminum high-temperature alloy material according to claim 1, characterized in that: in, The mass percentage of carbon element is 0.45-0.55wt%, the mass percentage of manganese element is below 0.5wt%, the mass percentage of silicon element is 0.5-0.9wt%, the mass percentage of chromium element is 24-31wt%, the mass percentage of nickel element is 44-47wt%, the mass percentage of aluminum element is 3.5-4.5wt%, the mass percentage of niobium element is 0.7-0.9wt%, the mass percentage of titanium element is 0.1-0.15wt%, the mass percentage of tungsten element is 0.5-0.8wt%, and the mass percentage of tantalum element is 0.1-0.2wt%. The mass percentage of zirconium element is 0.05-0.1wt%, the mass percentage of yttrium element is 0.05-0.1wt%, the mass percentage of cerium element is 0.05-0.1wt%, the mass percentage of molybdenum element is 0.05-0.5wt%, the mass percentage of nitrogen element is 0.05-0.1wt%, the mass percentage of hafnium element is 0.05-0.1wt%, the mass percentage of calcium element is 0.01-0.2wt% and the remainder of iron excluding impurities, the mass percentage of impurities is less than 130ppm, including less than 30ppm of sulfur element and less than 100ppm of phosphorus element.
5. The iron-chromium-nickel-aluminum high-temperature alloy material according to claim 1, characterized in that: in, The mass percentage of carbon is 0.42wt%, the mass percentage of manganese is 0.1wt%, the mass percentage of silicon is 0.41wt%, the mass percentage of chromium is 25wt%, the mass percentage of nickel is 45.1wt%, the mass percentage of aluminum is 4.0wt%, the mass percentage of niobium is 0.9wt%, the mass percentage of titanium is 0.11wt%, the mass percentage of tungsten is 0.8wt%, and the mass percentage of tantalum is 0. .14wt%, the mass percentage of zirconium element is 0.06wt%, the mass percentage of yttrium element is 0.01wt%, the mass percentage of cerium element is 0.009wt%, the mass percentage of molybdenum element is 0.3wt%, the mass percentage of nitrogen element is 0.11wt%, the mass percentage of hafnium element is 0.012wt%, the mass percentage of calcium element is 0.012wt% and the remainder of iron excluding impurities, wherein the impurities include 21ppm of sulfur element and 200ppm of phosphorus element.
6. Use of the iron-chromium-nickel-aluminum high-temperature alloy material according to any one of claims 1 to 5 in an ethylene radiation furnace tube.
7. The use according to claim 6, comprising: The iron-chromium-nickel-aluminum high-temperature alloy material is formed into an ethylene radiation furnace tube and subjected to a pre-oxidation treatment.
8. The use according to claim 7, characterized in that: The pre-oxidation treatment is carried out at a temperature of 900° C. for a period of 12-36 hours.
9. The use according to claim 7, characterized in that: The oxygen partial pressure of the pre-oxidation is 10 -27 bar below.
Citation Information
Patent Citations
Cast alumina forming austenitic stainless steels
US8431072B2
Alumina forming iron base superalloy
US8815146B2
Precipitation strengthening high-carbon austenitic heat-resistance steel and preparation method thereof
CN106636842A
High-aluminum austenitic alloy with excellent high temperature corrosion resistance and creep resistance
CN112853155A
Nickel-chromium-iron-aluminum alloy with good machinability, creep property and corrosion resistance and application of nickel-chromium-iron-aluminum alloy
CN114746565A
Cited By
High-temperature-resistant austenite heat-resistant casting alloy material and application method thereof
CN120624894A
Iron-chromium-nickel-aluminum superalloy material and application method therefor
WO2026179640A1